Serodiagnosis of Anti-glomerular Basement Membrane Disease Using a Newly Developed Chemiluminescence Immunoassay - Kühnl, Alexander; Hartwig, Lea; Dähnrich, Cornelia; Schlumberger, Wolfgang (Frontiers in Medicine, 2022)
Circulating autoantibodies directed against the kidney glomerular basement membrane (GBM) antigens are important markers in the diagnosis and monitoring of autoimmune glomerulonephritides, including the classic Goodpasture's syndrome. Rapid and reliable diagnostic tools for the detection of anti-GBM autoantibodies are crucial as anti-GBM disease can progress rapidly and, if too late or incorrectly diagnosed, can have serious, even fatal consequences. The performance of the newly developed standardized chemiluminescence immunoassay (ChLIA) was evaluated in comparison with the established Anti-GBM ELISA (IgG) (EUROIMMUN). For the assessment of its diagnostic performance, sera from 67 clinically characterized anti-GBM disease patients and 221 disease controls were analyzed. The clinical sensitivity of the Anti-GBM ChLIA (IgG) reached 100% at a specificity of 98.6%. The Anti-GBM ELISA (IgG) performance was less sensitive (89.6%) without any positive findings in the control group, indicating a specificity of 100%. Both methods were homogeneous (κ = 0.901). The Anti-GBM ChLIA (IgG) represents a promising alternative tool for accurate anti-GBM assessment in routine diagnostic settings with the advantage of rapid turnaround time and fully automated random-access processing.